Geochemistry of mafic metamorphic rocks in the Lutzow-Holm Complex, East Antarctica: Implications for tectonic evolution - Suda, Yoshimitsu; Kagashima, Shin-ichi; Satish-Kumar, M.; Motoyoshi, Yoichi; Hiroi, Yoshikuni (National Institute of Polar Research, 2006)
P(論文) Mafic metamorphic rocks are widely distributed through the Lutzow-Holm Complex (LHC) of East Antarctica, as layers between or enclaves within metasedimentary and metaigneous lithologies. It has been inferred that the peak metamorphic grade of the LHC progressively increases in a southwestern direction from amphibolite-facies to granulite-facies conditions, with mineral assemblages in the mafic metamorphic rocks changing from hornblende (magnesiohornblende)±biotite+plagioclase to orthopyroxene+clinopyroxene±hornblende (pargasite, magnesiohasting-site and tschermakite)±biotite±garnet+plagioclase. Field relationships suggest that amphibolite-grade mafic metamorphic rocks derive from mafic magma intruded into metasedimentary units, whereas granulite-facies mafic metamorphic rocks are a mixture of detrital blocks and mafic sill or intrusions. Major and trace element compositions of mafic metamorphic rocks are similar to those of igneous rocks of tholeiite affinity, and can be divided into volcanic-arc basalt (VAB)-type or mid-ocean ridge basalt (MORB)-type compositions. On a regional scale, VAB-type lithologies are predominant in amphibolite-facies areas, and MORB-type lithologies predominate in granulite-facies areas. On the basis of HFSE concentrations and Nb/Y ratios, MORB-type lithologies have T-type and E-type MORB compositions with oceanic plateau basalt and back-arc basin basalt affinities, and are occasionally found in the field intercalated with metasedimentary layers, characteristic of magmatism and sedimentation cycles in a marginal sea basin setting. Such field relationships provide information on the tectonic environment of protolith formation in the LHC. Various crustal components have been amalgamated into a relatively narrow mobile belt, which was subjected to high-grade metamorphism during the final closure of oceanic basins as a result of continent-continent collision. departmental bulletin paper